A comparison analysis of logging cost between conventional and reduce impact logging practices - Abdul Samad, Abdul Rahim; Othman, Mohd Shahwahid; Mohd Ashhari, Zariyawati (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
The operational application of the ‘Logfisher’ technology and system were undertaken at Sungai Betis, Gua Musang Forest Reserve in 2007 as an alternative to existing logging technologies. It has since been widely accepted and acknowledged as an efficient and cost effective alternative to existing low and reduced impact logging technologies such as skyline, Mobile Tower Yarder and Helicopter. This paper examined the various committed new and improved logging activities ascribed in the Reduce-Impact Logging (RIL) particularly using ‘Logfisher’ rather than Conventional Logging (CL). The cost function of present value is developed to analyse the logging cost between these two types of harvesting systems. The result of this study shows that the cost constitutes under RIL is higher than under CL. Incremental average per ha total cost rose by 46.86% to RM13,576/ha. While the incremental average per m3 total cost increased by 57.41% to RM267.80/m3. With increasing fuel prices and other cost related to labour, the logging cost is expected to increase in the near future. This situation will have adverse affect on the profitability of the practice of Sustainable Forest Management (SFM).